Evaluation of Planning, Implementation, and Assessment of Islamic Religious Education Learning in State Elementary School - Suwarni Jayanti; Ma'rifah Ma'rifah; Nurrahma Nurrahma; Amalia Syurgawi; Muh. Natsir (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study aims to evaluate the planning, implementation, and assessment of Islamic Religious Education (PAI) learning at 193 Barru State Elementary School. The research uses a descriptive qualitative approach to gain an in-depth and contextual understanding of PAI learning practices that take place in schools. Data was collected through observation, in-depth interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing using source and method triangulation techniques. The results of the study show that the PAI learning plan has been prepared according to the curriculum and meets administrative completeness, but it is still normative and less innovative and not fully oriented to students. The implementation of learning is conducive and religious, but it is still dominated by a teacher-centered approach with limited variations in learning methods and media. Meanwhile, PAI learning assessments tend to focus on cognitive aspects, while affective and psychomotor assessments have not been carried out systematically and measurably. This research emphasizes the importance of developing more creative, participatory, and holistic PAI learning in order to be able to form students who have faith, noble character, and are able to practice Islamic teachings in daily life.